Potential Pharmacokinetics and Pharmacodynamics (PK-PD) Drug-Herbs Interactions (DHI) from Metformin and Traditional Medicines: A Literature Review - Pramesthi, Asri Dwi Endah Dewi; Lukitaningsih, Endang; Nugroho, Agung Endro (EManuscript Technologies, 2022)
Introduction: Metformin given together with herbs in order to optimizing its mechanism of actions. The effect might be positive and vice versa. Interaction might occur pharmacokinetics or pharmacodynamically. The study aimed to review potential interaction of metformin and some herbs with various pharmacological activities. Methods: This literature review was conducted by collecting articles with keywords Metformin, Herb-drug Interaction, drug interaction, pharmacokinetics, pharmacodynamics, and pharmacology from international databases such as Science Direct, PubMed, Springer Link, and Scopus up to 2021. Results: Metformin with its various uses such as antidiabetic agent, an agent for reducing weight for patients that sensitive or even resistant to insulin, patients with obesity, anti-tumor agent, anti-cancer potential agent, and also has anti-aging potential. Metformin could interacted with drugs, herbs, and also some bioactive isolate. The interaction might occurs pharmacokinetically or pharmacodynamically. Pharmacokinetics interactions occurred during distribution and also excretion via transporters that metformin transported with. This was shown as the elevated or lowered metformin levels in blood. Pharmacodynamic interactions can be seen as the lowering or elevated levels of glucose, HbA1c and even the lipid profile in blood or plasma. Conclusion: According to this literature review, Metformin have potential interaction with drugs, herbs, and also some bioactive isolate. The interactions occur pharmacokinetically or pharmacodynamically. This study can be used as a established familiarity with and understanding the potential HDIs from Metformin and herbal products. © 2022 Phcogj.Com. This is an open-access article distributed under the terms of the Creative Commons Attribution 4.0 International license.